O desafio das igrejas se fazerem inclusivas em face da grande apostasia juvenil - Silva, Daniel Kayan Sirtori Felix Lopes da (Universidade Federal de São Carlos, 2023)
The purpose of this study is to expose and analyze the facts that leave the new generations in conflict, bringing inclusion into the churches, so that they don't get along and end up abandoning their beliefs. To this end, quotes and opinions from various authors on the subject were used, as well as the author's point of view through his experience in the field. The main objective of the work was to analyze the reasons for apostasy among young people in the church, examining why they have become more inclusive and their new nuances. The secondary objectives included conceptualizing and delimiting the new generations of believers and non-believers, studying the friction between them and understanding the churches' methods of reaching them. The methodology used was a bibliographical review, using books, articles and websites.
The challenge for churches to be inclusive in the face of the great youth apostasy
Keywords: Gerações; Igreja; Inclusão; Religião; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS